Oriented conversion of agricultural bio-waste to value-added products - A schematic review towards key nutrient circulation. (February 2022) - Ren, Liheng; Kong, Xiaoliang; Su, Jian; Zhao, Danyang; Dong, Wenjian; Liu, Chunmiao; Liu, Chao; Luo, Lin; Yan, Binghua
Graphical abstract: Highlights: Scheme of nutrient circulation during agricultural bio-waste conversion was proposed. Chemical conversion of straws to biochar and functional modification was evaluated. High value product recovery and carbon conversion through anaerobic digestion was summarized. Synergistic regulation of carbon/nitrogen loss during livestock waste composting was reviewed. Abstract: Agriculture bio-waste is one of the largest sectors for nutrient circulation and resource recovery. This review intends to summarize the possible scheme through coupling chemical conversion of crop straws to biochar and biological conversion of livestock waste to value-added products thus reaching key nutrient circulation. Chemical conversion of crop straws to biochar was reviewed through summarizing the preparation methods and functional modification of biochar. Then, high-solid two-phase anaerobic conversion of agriculture bio-waste to value-added products and improved performance of bio-conversion through byproduct gases reuse and biochar supplementation were reviewed. Finally, high quality compost production through amendment of biochar and residual digestate was proposed with analysis of reduced nitrogen emission and carbon balance. The biological mechanism of synergistic regulation of carbon and nitrogen loss during bio-conversion with biochar was also reviewed. This will provide a model for synergistic conversion of agricultural wastes to value added products pursuing key nutrient circulation.